2019
DOI: 10.4049/jimmunol.1900293
|View full text |Cite
|
Sign up to set email alerts
|

IRF7 Is Involved in Both STING and MAVS Mediating IFN-β Signaling in IRF3-Lacking Chickens

Abstract: IFN regulatory factor (IRF) 3 has been identified as the most critical regulator of both RNA and DNA virus–induced IFN production in mammals. However, ambiguity exists in research on chicken IRFs; in particular IRF3 seems to be missing in chickens, making IFN regulation in chickens unclear. In this study, we comprehensively investigated the potential IFN-related IRFs in chickens and showed that IRF7 is the most critical IFN-β regulator in chickens. With a chicken IRF7 (chIRF7) knockout DF-1 cell line, we condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 40 publications
2
50
0
Order By: Relevance
“…This leads to a subsequent signaling cascade via adaptor molecules and protein kinases that activate the key transcription factors (AP1, NF-κB and IRF7). The MAPK and PI3K/Akt pathways are potentially engaged in this signaling module in addition to the classical type I IFN induction pathway activating IRF7 by IkB kinases (IKK) TBK1 (TANK binding kinase 1), IKKε (IKBKE) or IKKα (CHUK) [13,57,58]. Overall, our data argue that IRF7 is a major modulator of the host antiviral response, and that the transcription factors NF-κB and AP1 are also capable of regulating both IFNA and INFB in addition to the inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to a subsequent signaling cascade via adaptor molecules and protein kinases that activate the key transcription factors (AP1, NF-κB and IRF7). The MAPK and PI3K/Akt pathways are potentially engaged in this signaling module in addition to the classical type I IFN induction pathway activating IRF7 by IkB kinases (IKK) TBK1 (TANK binding kinase 1), IKKε (IKBKE) or IKKα (CHUK) [13,57,58]. Overall, our data argue that IRF7 is a major modulator of the host antiviral response, and that the transcription factors NF-κB and AP1 are also capable of regulating both IFNA and INFB in addition to the inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The coordination of Interferon Regulatory Factor 7 (IRF7) and IRF3 on the initiation of the type I interferon (IFN) response to establish the antiviral state is well characterized in mammals; however, chickens may utilize a different modulation system due to a smaller repertoire of immune-related genes in avian species [9,10]. Particularly, chickens are missing IRF3, and only have IRF7, which has less than 40% of amino acid sequence identity to its mammalian orthologues [11][12][13]. Therefore, studying the chicken IRF7 could be a great starting point to elucidate the underlying cellular mechanisms of host immune regulation against AIV in chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, C-terminal tails of chicken, duck, and goose STING bore pLxIS motif, pointing to conserved actions of TBK1-mediated phosphorylation and binding of IRF7 (IRF3 is absent in avians) to promote downstream signaling ( Figure S16) [175]. In line with this, deletion of pLxIS motif (SLQxSyS motif) in the C-terminal tail of chicken STING led to failure to activate downstream IRF7 and IFN-β promoter [175].…”
Section: Stingmentioning
confidence: 83%
“…Upon phosphorylation from TBK1 activated by STING, IRF7 dimerizes and translocates to the nuclei, acting as a transcription factor. The dipolymer complex of IRF7 can then bind to the IRF7 receptor sites within the IFN-β promoter region, eventually activating the transcription of the IFN-β gene [69]. Therefore, I verified whether DEV could inhibit IRF7-stimulated IFN-β promoter activity.…”
Section: Dev Could Inhibit the Activation Of Duck Ifn-βmentioning
confidence: 91%
“…The transcriptional expression of IFN-β is regulated by the transcriptional enhancer bound to its promoter, which includes the regulatory region of IRF3/IRF7, AP-1 (activating protein 1), and the regulatory region of NF-κB. Intriguingly, in spite of IRF3 deficiency in chicken, poultries may employ IRF7 to reconstitute corresponding IFN signaling to respond to both DNA and RNA viral infections [69]. Therefore, in this study, for the first time we identified that VP16 could directly interact with duck IRF7 whereby the VP16 of DEV plays a vital role in antagonizing the innate immune system, assisting DEV virus to counteract this antiviral activity.…”
Section: Introductionmentioning
confidence: 99%